AN ANALYSIS : RELATIONSHIP BETWEEN WORKLOAD AND MENTAL HEALTH ON HEATHCARE WORKERS - Salsabila, Zulfi Fathiya; Dharmastiti, Rini (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2024)
Mental health is an important part in addition to physical health. Mental health problems are also faced by health workers due to the relatively high burden in their work. Based on the targets of the Sustainable Development Goals (SDGs), mental health is one of the areas of health and well-being. On the other hand, excessive workload is a source of fatigue, which is the root of burnout. The purpose of this study is to analyze the relationship between workload and mental health of health workers in a hospital. This study used a non-experimental method, namely cross sectional. Data were obtained from 49 respondents through a survey using an online questionnaire distributed by convenience sampling method. Respondents consisted of doctors (specialist and general), nurses, midwives, and pharmaceutical technical personnel. The workload questionnaire was adopted from the NASA-TLX, while mental health used the MBI-TBI. Relationship analysis was conducted using PLS-SEM using SmartPLS 4.0. The workload results obtained from this study were 65.87 or in the high category, with an allocation of very high workload of 27%, high as much as 53%, somewhat high 18%, and medium 2% of the total respondents. Factors related to mental load, physical load, and effort are the most dominant factors. The results for mental health obtained that emotional exhaustion in health workers is in the medium category (51%), personal achievement in the high category (80%), and for depersonalization in the high category (57%). The results of the correlation test between workload and the three factors on mental health found that workload has a significant relationship with the factors of emotional exhaustion and depersonalization (cynicism) with a probability of both <0.005, namely 0.000 and 0.001. The results of this study indicate that workload in health workers affects mental health, namely emotional exhaustion by 0.457 and depersonalization by 0.397. Thus, in order to maintain the mental health of health workers, intervention recommendations need to be made according to the results of this study.workload; mental health; healthcare workers, NASA-TLX; PLS-SEM